PENGABDIAN MAHASISWA/I KKN MBKM DI DESA SAWAH TAHUN 2024 - Mardes, Siska; Putri, Erika; Febriani, Nadila; Syafitri, Novia Nur; Safitri, Gladis Zulita; Ulva, Silvy Jelita; Risnawandari, Dini; Wanda, Evry (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Basically, Community Service (KKN) is a form of real service from students to the community after receiving lecture material that can always be useful in the community itself. Community service is an effort to disseminate knowledge, technology and art to the community. The Sawah Village community is a community that has various tribes and cultures with the majority being the Ocu Malay Tribe. The life of the community in Sawah Village is harmonious and peaceful even though there are differences in tribes. The form of service of the MBKM University of Riau 2024 Sawah Village KKN Group conducts teaching at schools in Sawah Village as an effort to improve the quality of education by bringing new innovations in teaching.